2021
DOI: 10.1021/acscatal.1c00732
|View full text |Cite
|
Sign up to set email alerts
|

Dearomatization of Unactivated Arenes via Catalytic Hydroalkylation

Abstract: The dearomative cyclization of linear amides to complex spirocyclic butyrolactams has been enabled by photoredox catalysis through a reductive radical–polar crossover mechanism. This mechanism operates with precision on unactivated aromatic substrates to give a wide range of 1,4-hydroalkylation products. This method utilizes a simple organic catalyst/reductant pair to deliver products in a highly flexible manner with respect to substitution, and the products can be further functionalized under simple condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 32 publications
5
27
0
Order By: Relevance
“…Beyond the immediate synthetic utility, these results are important because they challenge the notion that the terminal reductant can be viewed as merely an electron-source to turn over the photocatalyst. These data fit within a growing body of literature that suggests terminal reductant byproducts can play a non-innocent role in photoredox catalysis. ,, We suspect that these results could also offer an alternative explanation for recent examples wherein isophthalonitrile catalysts have appeared to reduce substrates beyond their expected redox potentials , and, more broadly, illustrate the importance of radical ion intermediates in photoredox catalysis.…”
supporting
confidence: 84%
“…Beyond the immediate synthetic utility, these results are important because they challenge the notion that the terminal reductant can be viewed as merely an electron-source to turn over the photocatalyst. These data fit within a growing body of literature that suggests terminal reductant byproducts can play a non-innocent role in photoredox catalysis. ,, We suspect that these results could also offer an alternative explanation for recent examples wherein isophthalonitrile catalysts have appeared to reduce substrates beyond their expected redox potentials , and, more broadly, illustrate the importance of radical ion intermediates in photoredox catalysis.…”
supporting
confidence: 84%
“…In line with their continuing interest in visible-light induced dearomatization, a-chloroacetamide bearing a pendant arene ring 57 was introduced as the substrate to realize an intramolecular dearomative hydroalkylation of arenes in the presence of a photocatalyst (Scheme 18). 52 This reductive radical-polar crossover methodology was further extended to the dearomative hydroarylation of aryl chlorides to produce spirocyclic cyclohexadienes by utilizing 3CzEPAIPN [2,4,5tri(9H-carbazol-9-yl)-6-(ethyl(phenyl)amino)isophthalonitrile] as the photocatalyst, probably through a ConPET protocol. 53 In 2021, Murakami et al reported an elegant dearomatization reaction induced by visible light via a three-component coupling process of arylphosphines, alkenes and water (Scheme 19).…”
Section: Shu-li Youmentioning
confidence: 99%
“…Here, the net addition of a hydrogen atom could reasonably be accomplished via concerted hydrogen atom transfer (HAT) or through a stepwise radical-polar crossover process (sequential addition of an electron and proton). We recently reported that radical-polar crossover effectively enables the dearomative spirocyclization of aryl and alkyl radical species. In this report, we share the initial insights that led to this program.…”
mentioning
confidence: 99%
“…This initial example of radical benzene dearomatization led to a broad method for the dearomatization of unactivated arenes through hydroarylation . Additional work has been done in our lab to extend this method to the dearomative hydroalkylation of unactivated arenes via α-acyl radical intermediates, and Yu detailed that anion trapping can be performed effectively with CO 2 …”
mentioning
confidence: 99%